Phylogenetic placement and redescription of the spider genus Atelidea Simon, 1895 (Araneae, Tetragnathidae) - Álvarez-Padilla, Fernando; Benjamin, Suresh P. (Zootaxa, 2011)
The spider genus Atelidea Simon, 1895 previously included two described species, A. spinosa Simon, 1895 and A. globosa Yamaguchi, 1957. In this study we describe for the first time the female of A. spinosa, and provide illustrations and scanning electron microscope images of external and internal features. The phylogenetic placement of this genus was investigated by including A. spinosa in a recent phylogenetic analysis with 23 tetragnathids. Parsimony analyses under equal and implied weights were performed. Our results suggest that Atelidea belongs to Tetragnathidae and in particular nests within Leucauginae, this last node is well supported and expected to endure future analysis; however, the relationships of Atelidea to other leucaugine species and its validity as a genus need to be assessed in future studies with a larger sample of leucaugine taxa. The second species described in the genus, A. globosa, is only known from its now lost type specimen from Japan and it is proposed as a nomen dubium leaving Atelidea monotypic.